Connection Fluor Albus With It Happens Abortion Imminens In Pregnant Women In The First Trimester At Wava Husada Hospital, Kesamben, Blitar District - Novena Aza Puspitasari (Universitas STRADA Indonesia, 2025)
Imminent abortion is vaginal bleeding at less than 20 weeks of gestation. The incidence of imminens abortion in the Indonesian Health Profile Information reached 1280 cases which were caused by reproductive health problems, one of which was vaginal discharge and vaginal discharge was also caused by poor personal hygiene in women or pregnant women. This study aims to determine the relationship between Albus Fluoride in Pregnant Women in the 1st Trimester and the occurrence of Imminent Abortion. The research design used in this study was analytical Correlation with Retrospective Study, sampling in this study used a simple random sampling method by taking 38 patients from 1st trimester pregnant women who experienced Imminent Abortion from January to December. Based on the analysis carried out using cross tabulation from the Spearman Test, it can be shown that a significant value of 0.000 is obtained, meaning that there is a significant relationship between Albus Fluoride in Pregnant Women in the 1st Trimester and the occurrence of Imminent Abortion at Wava Husada Kesamben Hospital. From the results of this research and calculations, it is hoped that midwives can be more active in providing knowledge regarding good personal hygiene and also how to prevent vaginal discharge in pregnant women.